Comparative Study in Attitudes towards the Covid-19 Vaccine According to Locus of Control (Internal - External) of University Students (Journal Of Educational and Psychological Researches, 2023)
AbstractThe current research aims to identify the attitudes towards the Covid-19 vaccine and the Locus of Control (internal, external) among university students, to identify the significance of the difference in attitudes towards the Covid-19 vaccine, the significance of the difference in the Locus of Control (internal, external) according to the gender variable (male, female), and to identify the significance of the difference in students’ attitudes towards Covid-19 vaccine according to the Locus of Control (internal, external). To achieve the objective of the research, the researcher developed two scales, a scale of (20) items to identify the attitudes toward a covid-19 vaccine, and a scale of the locus of control (internal-external) consisting of (22) items. The researcher applied the two scales to a sample of (300) male and female students, and the data was processed using the appropriate statistical methods. The results showed that university students have positive attitudes toward the Covid-19 vaccine in general and have an internal Locus of Control. The results also showed that there are no differences between males and females in attitudes towards the Covid-19 vaccine and in the Locus of Control (internal, external). Moreover, the results showed that there are differences between those with the internal Locus of Control and those with the external Locus of Control in attitudes towards the Covid-19 vaccine in favor of those with the internal Locus of Control, this implies that students with the internal Locus of Control have positive attitudes towards the vaccine compared to students with the external Locus of Control which their attitudes towards Covid-19 vaccine were negative. In light of these results, the researcher presented a set of recommendations and suggestions for conducting future research.